Trigonidiinae crickets from Rodrigues island: from widespread pantropical species to critically endangered endemic species - Hugel, Sylvain (Zootaxa, 2012)
The Trigonidiinae crickets of Rodrigues are examined. Two species widespread in South Western Indian Ocean islandsare recorded in Rodrigues for the first time: Trigonidium cicindeloides Rambur, 1839 and Natula longipennis (Serville,1839). Nemobius luteolus Butler, 1876 is a Trigonidiinae and not a Nemobiinae, it is transferred to Metioche Stål, 1877 asMetioche luteolus (Butler, 1876), n. comb. Two new species are described from the restored areas of the island. Thesenew species are tentatively considered as Metioche and included in the new subgenus Superstes n. subgen.: Metioche (Su-perstes) superbus n. subgen., n. sp. and Metioche (Superstes) payendeei n. subgen., n. sp. This new subgenus is charac-terized by the male genitalia asymmetry and the striking hyperthely of the left pseudepiphallic lophi and paramere. Elements of the ecology of endemic Trigonidiinae of Rodrigues are given, and their conservation status is assessed.